Benign chondroblastoma on fine‐needle aspiration smears: A seven‐case experience and review of the literature. Issue 9 (25th April 2015) - Cozzolino, Immacolata; Zeppa, Pio; Zabatta, Assunta; Merolla, Francesco; Vetrani, Antonio; Sadile, Francesco
<x xml:space="preserve">Abstract</x> We report seven cases of chondroblastoma (CB) of bone, diagnosed by Fine‐Needle Aspiration Cytology (FNAC), and confirmed by histomorphological examination. The concurrence of some cytomorphologic findings — mononucleated cells, multinucleated cells, and intercellular chondroid substance — unequivocally suggested the cytological diagnosis of CB. We also reviewed the literature on this topic in order to discuss morphological criteria and the importance of needle size. The differential diagnosis between CB, Giant Cell Tumor of Bone, and Eosinophilic Granuloma is further discussed. Diagn. Cytopathol. 2015;43:734–738. © 2015 Wiley Periodicals, Inc.